2016
DOI: 10.1159/000443368
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance to EGFR Inhibitors in Lung Cancer

Abstract: Background: The discovery of mutations in epidermal growth factor receptor (EGFR) has dramatically changed the treatment of patients with non-small-cell lung cancer (NSCLC), the leading cause of cancer deaths worldwide. EGFR-targeted therapies show considerable promise, but drug resistance has become a substantial issue. Methods: We reviewed the literature to provide an overview of the drug resistance to EGFR tyrosine kinase inhibitors (TKIs) in NSCLC. Results: The mechanisms causing primary, acquired and pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 129 publications
(226 reference statements)
1
50
0
Order By: Relevance
“…Nearly 50% of these patients fail due to the fact that chemotherapy cannot prevent a relapse. Reasons for treatment failure are an intrinsic resistance or the development of an acquired resistance under treatment [24]. Active drug efflux transporters of the adenosine triphosphate binding cassette (ABC) are involved in transport processes for a variety of drugs used in chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 50% of these patients fail due to the fact that chemotherapy cannot prevent a relapse. Reasons for treatment failure are an intrinsic resistance or the development of an acquired resistance under treatment [24]. Active drug efflux transporters of the adenosine triphosphate binding cassette (ABC) are involved in transport processes for a variety of drugs used in chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Second, afatinib has the potential to affect NSCLC, which is resistant to gefitinib and erlotinib. In recent years, drug resistance has become a substantial issue [27]. The study of LUX-Lung 4 demonstrated that some patients who had acquired resistance to gefitinib and/or erlotinib could receive benefit from afatinib, with a median progression-free survival of 4.4 months and an objective response rate of 8.2% [28].…”
Section: Discussionmentioning
confidence: 99%
“…6 Acquired resistance mechanisms to the firstand second-generation EGFR TKIs erlotinib, gefitinib, and afatinib have been well described, with the EGFR T790M mutation driving resistance in at least half of patients. [7][8][9] The activation of bypass pathways has also been observed as a potential mechanism of resistance to EGFR TKIs, and involves multiple pathways of at least 4 different types of alterations in multiple genes, including focal copy number amplifications in MET, ERBB2 (HER2), or ERBB3; missense mutations in BRAF, MAP2K1 (MEK1), PIK3CA, or KRAS; inactivating mutations or allelic loss in PTEN or RB1 (the latter a hallmark of epithelial-mesenchymal transition to a small-cell phenotype), and fusions in ALK. [7][8][9] The third-generation EGFR TKIs osimertinib and rociletinib inhibit both EGFR activating and T790M mutations, and have demonstrated activity in NSCLC patients with disease that progressed while receiving therapy with firstor second-generation EGFR inhibitors.…”
Section: Introductionmentioning
confidence: 99%